The impact of SimMan on resident training in emergency skills. Issue 2 (January 2019) - Liu, Yu; Zhang, Yanshu; Zhang, Lei; Bai, Hongliang; Wang, Gang; Guo, Litao
Abstract : Abstract: The purpose of this study was to analyze the role of SimMan in resident training of emergency skills. Forty-five 1st year medical residents were selected for this study. All participants were divided into groups and each participant performed different roles during training. Clinical cases were selected using the tutor mode/auto mode in the SimMan computer system in order to train and assess each group. A pre-test was administered to the 45 residents before emergency medical technician (EMT) skill training. Finally, a post-test was conducted with SimMan after training. Tutors scored the student's performance and recorded the overall time for the procedure. Before training, the overall qualification rate was 44.44%. The average score of the 9 groups was 62.78 ± 8.84 and the average 1st aid duration was 519.22 ± 34.35 seconds. After the training, the overall qualification rate was 100%. The average score of the 9 groups was 80.89 ± 7.39. The average 1st aid duration was 453.56 ± 24.40 seconds. The P values in comparing pre- and post-training data were .009, <.001 and <.001. An integrated learning approach using SimMan as a tool for training and examination can help training residents develop emergency skills, teamwork, and communication.